Coupled multi-physics simulation of chloride diffusion in saturated and unsaturated concrete. (19th July 2021) - Zhang, Ying; Luzio, Giovanni Di; Alnaggar, Mohammed
Highlights: Cl ion diffusion is fully coupled with heat transfer, mass transport and aging. Pore solution chemistry, concentration, and pore structure aging are considered. Thermal effects on diffusivity and Cl binding capacity are included. Cl profile is predicted with varying time, temperature, concentration, and humidity. A critical balance between modeled physics and model robustness is achieved. Abstract: Chloride-induced corrosion of steel reinforcement is one of the major long-term deterioration mechanisms for reinforced concrete infrastructures. Chloride transport through cement-based materials is a complex chemo-physical process involving ionic diffusion in concentrated solution, pore structure, chemistry, membrane permeability of the matrix, cracking, and the variation of the internal and external environmental conditions. Although in the literature there are plenty of both simplistic phenomenological models and sophisticated models, in this study, a new model is developed taking aim at capturing the fundamental physics and, at the same time, having a formulation as simple as possible that it can be effectively calibrated and validated using available limited experimental data. The model couples the ionic diffusion process with the concrete micro-structure evolution due to continued hydration accounting for hygro-thermal variations and their effects on both the diffusion and hydration processes. The formulation is implemented in a semi-discrete conduit transport network that mimics the internal heterogeneity of the cementitious material by connecting the matrix space between coarse aggregate pieces. This allows the model to replicate naturally the meso-scale tortuosity effect which is an important feature towards representing realistically the heterogeneity-induced variations of chloride concentration within the concrete. The limited model parameters are carefully calibrated and the formulation is validated by simulating multiple experiments ranging from diffusion through pastes to large concrete cylinders. The results of numerical simulations show the ability of the model to describe spatial and temporal evolution of the chloride concentration within the samples under varying chloride concentrations and temperature boundary conditions within both saturated and unsaturated concrete.